INTELLIGENT CONTROLLER-BASED DYNAMIC VOLTAGE RESTORER TO REDUCE THE VOLTAGE FLUCTUATIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
In today's power system research, improving power quality is a crucial issue. Due to the advent of numerous industrial equipment and sensitive loads, it has become increasingly vital. Distribution-side voltage sags and swells are the leading causes of power quality issues. Five-level multilevel inverters are too expensive for average-voltage applications and high-power applications due to higher voltage stress on switches, large dv/dt, and the need for extensive filtering. The proposed seven-level multilevel inverter-based dynamic voltage restorer (DVR) is a superior solution to these issues because it can be directly connected to the medium-voltage distribution system without an injection transformer. There are numerous ways to reduce voltage sags and swells, but the planned DVR is one of the most widely used techniques. As a series compensating device, the DVR is primarily used in applications involving low- and medium-voltage systems and employs a fuzzy logic controller (FLC)- based Proportional and Integral (PI) controller to compensate for voltage sags during a three-phase fault. Using simulation results from a fresh DVR setup available in MATLAB/Simulink, the effectiveness and performance of the proposed model are confirmed.
Keywords: Fuzzy logic controller (FLC); Proportional integral (PI); Dynamic voltage restorer (DVR); Total harmonics distortion (THD); Cascade H-bridge (CHB); Pulse width modulation (PWM)